Instant city : life and death in Karachi - Inskeep, Steve (New York : Penguin Press, 2011)
Analyzes the growing metropolis of Karachi, Pakistan, including the importance of regional stability to American security interests, the terrorist bombing of a Shia religious procession, and the challenging religious, ethnic, and political divides.
Includes bibliographical references and index.
Keywords: Karachi (Pakistan) -- Social conditions